2020
DOI: 10.1094/phyto-11-19-0419-r
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Manures and Manure-Based Composts on Root Lesion Nematodes and Verticillium dahliae in Michigan Potatoes

Abstract: The interaction of the root lesion nematode Pratylenchus penetrans and the fungal plant pathogen Verticillium dahliae causes potato early die (PED) complex, which induces premature vine senescence and dramatically reduces yield in potatoes. Management of PED is often achieved through the use of soil fumigants and nematicides, but their adverse effects on soil, human and environmental health, and strict regulations worldwide require alternative control tactics. In this study, we investigated the effects of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Microbial communities produce volatile fatty acids (VFAs) during the decomposition process of manure-based composts, which act as a mechanism of control (Cole et al, 2020). Studies have demonstrated that even small concentrations of VFAs found in liquid swine manure can have lethal effects on V. dahliae and nematodes (Cole et al, 2020).…”
Section: Treatments Effect On the Soil Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…Microbial communities produce volatile fatty acids (VFAs) during the decomposition process of manure-based composts, which act as a mechanism of control (Cole et al, 2020). Studies have demonstrated that even small concentrations of VFAs found in liquid swine manure can have lethal effects on V. dahliae and nematodes (Cole et al, 2020).…”
Section: Treatments Effect On the Soil Microbiomementioning
confidence: 99%
“…Microbial communities produce volatile fatty acids (VFAs) during the decomposition process of manure-based composts, which act as a mechanism of control (Cole et al, 2020). Studies have demonstrated that even small concentrations of VFAs found in liquid swine manure can have lethal effects on V. dahliae and nematodes (Cole et al, 2020). Unfortunately, the majority of VFAs do not exhibit long-term persistence within composts or manures, due to their rapid breakdown by microorganisms, degradation, or absorption, which significantly reduces their antagonistic properties over time (Cole et al, 2020).…”
Section: Treatments Effect On the Soil Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…After being applied to soil, most organic amendments need to be further decomposed and turned into various small molecules through a process of microbial degradation before taking effect, although some of them are active elements that affect plant growth and soilborne pathogens immediately. Compost is unique because it is ready to use, as most organic matter that it is composed of is already degraded [ 90 ].…”
Section: Soil Amendment For Disease Management—from Practice To Promisementioning
confidence: 99%
“…Fatty acids were more easily released from the fertilizer when applied to dry and heated soil (Conn et al 2004). Cole et al (2020) demonstrated that poultry manure could be a promising amendment to control potato early die complex which induces premature vine senescence and dramatically reduces yield in potatoes. The disease is caused by complex of V. dahliae and nematode Pratylenchus penetrans.…”
Section: Addition Of Organic Amendmentsmentioning
confidence: 99%